In vitro antiviral efficacy of caffeic acid against canine distemper virus. (September 2017) - Wu, Zong-Mei; Yu, Zhen-Jiang; Cui, Zhen-Qiang; Peng, Lu-Yuan; Li, Hao-Ran; Zhang, Chun-Lei; Shen, Hai-Qing; Yi, Peng-Fei; Fu, Ben-Dong
Abstract: Canine distemper (CD) is a highly contagious disease caused by the canine distemper virus (CDV), and mortality can be as high as 100%. However, there is no specific treatment for CD. In this study, the antiviral activity of the caffeic acid against CDV was evaluated in vitro. The results showed that the IC50 of the caffeic acid against CDV at 1 and 2 h post infection (PI) is 23.3 and 32.3 μg/mL, respectively. Consistently, at 1 and 2 h PI, the caffeic acid exhibited a reduced (23.3–57.0% and 37.2–38.1%) viral inhibitory effect in vero cells. Furthermore, the caffeic acid plus Ribavirin (RBV) has greater antiviral activity against CDV than the caffeic acid or RBV individually. In addition, the caffeic acid reduced the total viral RNA synthesis by 59–86% at 24-72 h. Therefore, our data provided the experimental evidence that the caffeic acid effectively inhibited CDV infection in vero cells, which may potentially be used to treat clinical disease associated with CDV infection. Graphical abstract: Highlights: The antiviral activity of the caffeic acid against CDV was evaluated in vero cells. The caffeic acid inhibits viral RNA accumulation during CDV replication cycle. The caffeic acid plus RBV inhibited the viral intracellular and extracellular stage of replicative cycle.